Multicentre study of investigation and management of inpatient hyponatraemia in the UK. Issue 1070 (14th November 2014) - Tzoulis, Ploutarchos; Evans, Rhys; Falinska, Agnieszka; Barnard, Maria; Tan, Tricia; Woolman, Emma; Leyland, Rebecca; Martin, Nick; Edwards, Rebecca; Scott, Rebecca; Gurazada, Kalyan; Parsons, Marie; et al.
Abstract: Purpose: Hyponatraemia is associated with significant morbidity and mortality. The objectives of this study were to evaluate the investigation and management of hyponatraemia and to assess the use of different therapeutic modalities and their effectiveness in routine practice. Study design: This multicentre, retrospective, observational study was conducted at three acute NHS Trusts in March 2013. A retrospective chart review was performed on the first 100 inpatients with serum sodium (sNa) ≤128 mmol/L during hospitalisation. Results: One hundred patients (47 male, 53 female) with a mean±SD age of 71.3±15.4 years and nadir sNa of 123.4±4.3 mmol/L were included. Only 23/100 (23%) had measurements of paired serum and urine osmolality and sodium, while 31% had an assessment of adrenal reserve. The aetiology of hyponatraemia was unrecorded in 58% of cases. The mean length of hospital stay was 17.5 days with an inpatient mortality rate of 16%. At hospital discharge, 53/84 (63.1%) patients had persistent hyponatraemia, including 20/84 (23.8%) with sNa <130 mmol/L. Overall 37/100 (37%) patients did not have any treatment for hyponatraemia. Among 76 therapeutic episodes, the most commonly used treatment modalities were isotonic saline in 38/76 cases (50%) and fluid restriction in 16/76 (21.1%). Fluid restriction failed to increase sNa by >1 mmol/L/day in 8/10 (80%) cases compared with 4/26 (15.4%) for isotonic saline. Conclusions: Underinvestigation and undertreatment of hyponatraemia is a common occurrence in UK clinical practice. Therefore, development of UK guidelines and introduction of electronic alerts for hyponatraemia should be considered to improve clinical practice.